Beware of cyberbullying! Evidence from high school students in Indonesia - Fredik Lambertus Kollo; Zulkarnain Zulkarnain; Tuatul Mahfud; Matang Matang (Institute of Advanced Engineering and Science, 2024)
Cases of cyberbullying among high school students have become the center of attention of educational institutions as a new form of bullying using information technology. Many studies examine cyberbullying as a new form of bullying. However, studies on school climate, social support, and social self-efficacy in reducing cyberbullying behavior among high school students are still limited. Therefore, this study investigates the effect of school climate, social support, and social self-efficacy on cyberbullying behavior. This study involved 290 high school students in three schools in Kupang City, Indonesia. We used a simple random sampling technique to determine which respondents were involved. SPSS version 20 and Amos 18 software were used to analyze the data for this study. Data analysis in this study used structural equation modeling (SEM) analysis. The study’s results revealed that school climate and social self-efficacy significantly negatively affected high school students’ cyberbullying behavior. Meanwhile, social support has no direct influence on students’ cyberbullying behavior. Social self-efficacy has also been shown to mediate the effect of school climate on high school students’ cyberbullying behavior. An in-depth discussion is presented in this paper to provide an overview of the critical implications for educational practitioners.